Numerical Analysis of Brake Performance in Passenger Cars (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Brakes work when two different materials come into contact with the vehicle to reduce braking distance. Due to the irregularities located in the surface mechanism, it contacts with a high contact force and makes an annoying noise called brake squeal. This article examines braking distance based on research based on incorporating a brake isolator into the brake assembly to reduce noise. Different configurations of isolators are used in finite element analysis. The effectiveness of the brake isolator is analyzed using different types of isolators. The finite element model of the brake is developed on a real basis we can determine using the dimensions of the drum brake. Braking distance is used for modal analysis to estimate the modal. Frequencies and mode shapes must be considered. Different friction coefficients, wheel speeds and braking forces are taken into account in the analysis. The braking device is indicated by a positive real and the accompanying slip rate in the basic model of a part of the basic graph the isolator significantly increases the noise of brake noise. This results in increased braking distance.